2016
DOI: 10.1002/jms.3813
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–tandem mass spectrometry and passive sampling: powerful tools for the determination of emerging pollutants in water for human consumption

Abstract: Among the wide range of emerging pollutants, perfluorinated compounds and various pharmaceuticals, such as nonsteroidal anti-inflammatory drugs, are showing growing concern. These contaminants can be found in freshwater ecosystems because of their incomplete removal during wastewater treatments so, their water solubility and poor degradability result in their continuous discharge and pseudo-persistent contamination. Usually, expected levels of these analytes are particularly low; therefore, sensitive and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Also interestingly, AC originating from waste sources has been reported with noteworthy performance in the removal of some specific ECs such as Paracetamol [48], antibiotics [56], and anti-inflammatory drugs [42].…”
Section: Adsorption Using Activated Carbon (Ac)mentioning
confidence: 99%
“…Also interestingly, AC originating from waste sources has been reported with noteworthy performance in the removal of some specific ECs such as Paracetamol [48], antibiotics [56], and anti-inflammatory drugs [42].…”
Section: Adsorption Using Activated Carbon (Ac)mentioning
confidence: 99%
“…Numerous experiments have been carried out under laboratory conditions to explore the cumulative dynamics of samplers controlled by water membrane interface. It was found that there was a large deviation in the R s values obtained under in situ and laboratory conditions for the same pollutant [26,49,52]. This variability was mainly due to the diverse environmental conditions that have been poorly explored.…”
Section: Water Flow Ratementioning
confidence: 99%
“…The summary of R s values from 23 previous studies are presented in Figure 3. The further statistical analysis of data revealed a substantial positive correlation between water flow rate and the R s values due to the rise in diffusion rate and the decrease of WBL thickness by increasing turbulence [13,21,26,27,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. Not surprisingly, however, a significant variability was observed in the R s /A values, ranging from 4.73 × 10 −5 to 1.63 × 10 −1 L/cm 2 /d at flow rate from unstirring to 16.75 cm/s since different pH values, various temperatures, and diverse analytes were used in the calibration experiments from the literature [44,53,57,58].…”
Section: Water Flow Ratementioning
confidence: 99%
See 1 more Smart Citation
“…The problem of drug residues in WWTP effluents was addressed in the urban wastewater treatment directive of the EC, which has been continually updated since its release in 1991 [2]. Although WWTPs use several steps for the clean-up of wastewater, namely a pretreatment, a primary, a secondary and/or a tertiary/advanced treatment, contaminants may not be removed completely and can subsequently be found in the effluent [3][4][5][6][7][8][9][10][11][12]. This is of particular concern when the treated wastewater is reused, e.g., for irrigation in agriculture, an approach that has become common practice in many arid regions [13].…”
Section: Introductionmentioning
confidence: 99%